Será possível uma ética global?: entre as condições e os fundamentos - Brito, José Henrique Silveira de (Angelicum, 2012)
On the basis of the consensus concerning the need of a global ethics in the current context, this study presents a critique of some of the attemtps to offer philosophical foundation for such an ethics. It demostrates that the attempts do not go beyond a formal discourse and the seem to ignore that human beings necessarily dwell in determinate cultural contexts